Analisis efektifitas transmisi kebijakan moneter konvensional dan syariah dalam mempengaruhi tingkat inflasi - Heri Sudarsono (Jurnal Ekonomi & Keuangan Islam, 2017)
AbstractThe purpose of this research is to analysis the transmission mechanisme of dual monetary system from conventional and sharia to inflation (IHK) using Vector Auto Regression (VAR) methods. The data used in this study is monthly data in the form of time series began in January 2000 to December 2016. Data process employ stationer test, cointegration test, stability test, impulse response functions analysis and forecast error variance decomposition. The result of conventional transmission mechanisme shows that is SBMK effective to promote inflation, but SBI, LOAN, and PUAB are not effective to promote inflation. Meanwhile, the sharia transmission mechanisme indicate that are SBIS and FINCS not effective in drive inflation, while FINC and IHMK effective to boost inflation. Finally, in dual transmission mechanisme shows that LOAN and FINC contribute more than other variables in influencing inflation.